2023
DOI: 10.1186/s12889-022-14905-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine attitudes among a majority black sample in the Southern US: public health implications from a qualitative study

Abstract: Background The COVID-19 pandemic continues to have high caseloads in the US, with vaccines a critical component of the response. Disparities in COVID-19 morbidity and mortality have been identified across states and racial/ethnic groups, which are likely in part due to disparities in COVID-19 vaccine uptake. This study aims to better understand and contextualize COVID-19 vaccine hesitancy among persons from under-represented racial/ethnic populations in the Southern US. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our findings regarding barriers to vaccination among Black individuals with rheumatic conditions are congruent with previous studies among the general Black population (21–25). A recent qualitative study of Black churchgoers from a single congregation in Boston found lack of trust, rushed development, fear of side effects, history of medical mistreatment, and a perception of low risk as reasons for vaccine hesitancy in this group (26).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings regarding barriers to vaccination among Black individuals with rheumatic conditions are congruent with previous studies among the general Black population (21–25). A recent qualitative study of Black churchgoers from a single congregation in Boston found lack of trust, rushed development, fear of side effects, history of medical mistreatment, and a perception of low risk as reasons for vaccine hesitancy in this group (26).…”
Section: Discussionsupporting
confidence: 90%
“…This recommendation is consistent with other studies that identified the successful dissemination of health promotion messages, such as public health awareness campaigns involving social media influencers and celebrities of color ( Portacolone et al, 2020 ). Such collaborations effectively countered negative social media messages with positive messages that mirrored communities' discussions around vaccine uptake ( Bateman et al, 2022 ; Huang et al, 2022 ). In addition, our findings also underscored the value of resorting to one's own agency while finding inspiration and comfort in the words of Black/African American leaders, such as Martin Luther King, which provides insights into how public health and government officials can leverage Black/African American legacy and history to foster empowerment and rebuild trust ( Bunch, 2021 ; LaVeist et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the predictors of vaccine receptivity identified among Black/African Americans were high levels of mistrust stemming from historical and contemporary experiences of systemic racism against the Black community, structural barriers such as inaccessible vaccination sites, fear of the unknown, and lack of accurate information from trusted community and public health officials. Additional barriers to vaccine receptivity included the belief that the speed at which the vaccines were developed was evidence of intentions to harm the Black/African American community ( Dong et al, 2022 ; Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Huang et al, the main reasons for vaccination hesitancy were concerns about the safety of the COVID-19 vaccine and limited trust in the government [ 27 ]. Other researchers have also mentioned that ideology, which can result in the rejection of science due to conspiracist ideation and limited trust in government medical experts, is a factor that indirectly affects immunization propensity [ 10 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also mentioned that ideology, which can result in the rejection of science due to conspiracist ideation and limited trust in government medical experts, is a factor that indirectly affects immunization propensity [ 10 , 28 ]. Huang et al listed the presence of local vaccine distribution points among the factors contributing to vaccination [ 27 ]. In our study, respondents did not experience difficulties in reaching the vaccination points but faced challenges of other nature when receiving vaccines.…”
Section: Discussionmentioning
confidence: 99%